New insights provided by solvent relaxation NMR-measured surface area in liquids to explain phenolics sorption on silica nanoparticles. Issue 3 (23rd January 2017) - Zhang, L. W.; Li, H.; Chen, F. Y.; Zhang, D.; Wu, M.; Pan, B.; Xing, B. S.
Abstract : The surface area measured only in the circumstances relevant to the sorption system can be applied to understand the interfacial properties. Abstract : Although the Brunauer–Emmett–Teller (BET) measurement based on gas adsorption is the widely recognized method of characterizing the specific surface area (SSA) and pore structures, this method is limited to the analysis of dried particles, and thus has little relevance to the determination of the behavior and performance of those particles in liquids ( e.g., wetted surface). In this study, the BET-N2 surface area of dehydroxylated silica NPs was correlated with phenol and β-naphthol sorption in hexane, but not in water. Clearly, the BET-N2 surface area could not explain the sorption data. We measured the surface –OH density (nm −2 ) of silica NPs after hydroxylation and observed more –OH groups on surfaces of less curvature (bigger particle sizes), which may explain the higher sorption of phenolic chemicals on larger particles (but smaller surface area) through hydrogen bonding. The silica NPs were less aggregated after hydroxylation, which also contributed partly to the increased sorption after hydroxylation. Thus, the silica NP surface area measured in the dry state will not provide useful information to understand the actual sorption of phenolic chemicals. We applied a method based on solvent relaxation NMR to measure the silica NP (before and after hydroxylation) surface properties in different solvents to correlate with the sorption data. The sorption data in different solvents were more easily correlated with the relaxation data in the corresponding solvents. We thus call the readers' attention that the surface area measured only in the circumstances relevant to the sorption system can be applied to understand the interfacial properties.